International Legal Meaning of the Second Hague Peace Conference and the Role of Russia - O. Glikman (Международная аналитика, 2017)
The paper presents the historical legal context of the Second Hague Peace Conference (1907) and highlights the role played by Fyodor Fyodorovich (Friedrich Fromhold) Martens in the successful outcome of the Conference. A characteristic is given to various aspects of the influence which the documents signed at the Conference exerted on the development of International Law, as well as to key factors of its impact on the modern legal norms.